Discretionary Monetary Policy Versus Rules : The Japanese Experience During 1986-91 - Meredith, Guy (IMF Working Papers; Working Paper ;, 1992)
This paper compares the hypothetical performance of various monetary policy rules with that of the discretionary policies actually pursued in Japan over the 1986-91 period. The results suggest that simple rules based on targeting growth in either the money supply, nominal income, or prices would have failed to stabilize economic variables more successfully than discretionary policies. At the same time, it appears that an indicator of monetary conditions incorporating movements in the real exchange rate and the real interest rate would have been useful in assessing the effect of current policies on future activity.